Multidimensional transcriptomics based to illuminate the mechanisms of taurine metabolism in immune resistance of pancreatic cancer - Qin, Zongshuai; Huang, Guixiang; Xu, Jian; Pan, Lujuan; Lan, Chaojun; Yang, Yuhuan; Yin, Yixia; Qin, Yueqiu (Frontiers in Immunology, 2025)
Pancreatic cancer, a highly malignant tumor of the digestive system, is characterized by a tumor microenvironment with a high degree of immunosuppression. This immunosuppressive property poses significant challenges, as it hampers the effective infiltration of immune cells and impairs their ability to exert cytotoxic effects. The metabolic process of taurine has emerged as a crucial factor in modulating the functions and activities of immune cells. Intervening in taurine metabolism holds the potential to reshape the tumor immune microenvironment, thereby enhancing the ability of immune cells to recognize and eliminate tumor cells. To explore the potential therapeutic relationship between taurine metabolism disorders and pancreatic cancer immunotherapy, we employed multiple software packages, including “Seurat”, “DoubletFinder”, “Harmony”, “GSVA”, and “CellChat” to analyze single-cell data and spatial transcriptomic data of pancreatic cancer. In the present study, four distinct tumor cell subsets, namely RPS4Y1+ tumor cells, LYZ+ tumor cells, CPE+ tumor cells, and MKI67+ tumor cells, were identified for the first time. The CNV score and taurine metabolism score highlighted the significant role of RPS4Y1+ tumor cells within the immunosuppressive microenvironment of pancreatic cancer. Through cell-communication analysis, the crosstalk among fibroblasts, CD8+ T cells, and RPS4Y1+ tumor cells was identified, offering novel insights into immunotherapy strategies, which was strengthened by the co-localization analysis of spatial transcriptomics. Furthermore, by conducting a combined analysis of survival data, we identified LY6D as a potential therapeutic target. Through co-culture experiments with fibroblasts, we uncovered the underlying mechanism of LY6D in regulating taurine metabolism imbalance within the immunosuppressive microenvironment of pancreatic cancer. The establishment of the “taurine-immune crosstalk” criteria in this study effectively paves the way for pancreatic cancer immunotherapy. In conclusion, the current research underscores the significance of taurine metabolism in the immunosuppressive microenvironment of pancreatic cancer. Targeting taurine metabolism may represent a crucial approach for reversing the “stiff-cancer” characteristics of pancreatic cancer.